2023
DOI: 10.3389/fimmu.2023.1147379
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of macrophages inflammasome activation via autophagic degradation of HMGB1 by EGCG ameliorates HBV-induced liver injury and fibrosis

Abstract: BackgroundLiver fibrosis is a reversible wound-healing response that can lead to end-stage liver diseases without effective treatment, in which HBV infection is a major cause. However, the underlying mechanisms for the development of HBV-induced fibrosis remains elusive, and efficacious therapies for this disease are still lacking. In present investigation, we investigated the effect and mechanism of green tea polyphenol epigallocatechin-3-gallate (EGCG) on HBV-induced liver injury and fibrosis.MethodsThe effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…It has been reported that EGCG prevents liver inflammation, oxidative stress, and even fibrosis in CCl4-induced liver injury in mice [41]. EGCG treatment suppressed NLRP3 inflammasome in Kupffer cells, which resulted in the therapeutic effect of EGCG against HBV-induced liver injury [42]. Therefore, we speculated that the anti-inflammatory and hepatoprotective effects of CSL3 are due to EGCG.…”
Section: Discussionmentioning
confidence: 87%
“…It has been reported that EGCG prevents liver inflammation, oxidative stress, and even fibrosis in CCl4-induced liver injury in mice [41]. EGCG treatment suppressed NLRP3 inflammasome in Kupffer cells, which resulted in the therapeutic effect of EGCG against HBV-induced liver injury [42]. Therefore, we speculated that the anti-inflammatory and hepatoprotective effects of CSL3 are due to EGCG.…”
Section: Discussionmentioning
confidence: 87%
“…For example, complement factor C5a stimulates pro-inflammatory pathways via C5aR1 on macrophages, and C5aR1ko knockout mice showed a M1- to M2-type macrophage transition and reduced fibrosis in a MASH mouse model ( 122 ). HMBG1 secretion from injured hepatocytes induced NLRP3 inflammasome activation in macrophages ( 123 ), and fibrinogen-like protein 2 (Fgl2), which was upregulated in liver tissues of cirrhotic patients with underlying hepatitis C infection, promoted M1 polarization ( 124 ). Furthermore, autophagy triggered a M2-type, whereas LPS stimulation favored a M1-type macrophage polarization and blocked autophagy ( 125 ).…”
Section: The Role Of Macrophages In Fibrosis Initiation Progression A...mentioning
confidence: 99%
“… 17 Downregulation of SIRT1 in senescent hepatocytes reportedly exacerbates carbon tetrachloride (CCl 4 )-induced and alcohol-induced liver injury and fibrosis in aged mice 4 , 5 ; however, whether HMGB1 is involved in this process is unknown. In addition, HMGB1 is primarily secreted by damaged hepatocytes in CLD, 18 and current studies mostly concentrate on how extracellular HMGB1 activates HSCs in liver fibrosis. 19 However, the effects of HMGB1 on other hepatic nonparenchymal cells and the role of circulating HMGB1 are partially understood.…”
Section: Introductionmentioning
confidence: 99%